Intrastate conflict and social space in a critical realist perspective: a quantitative analysis of the formation of non-state actors and of profiles of violence in Asia and Oceania - Wencker, Thomas (2018)
Departing from the position of critical realism, a comprehensive analysis of social ontology, and a close examination of existing research, the first part of the dissertation brings forward new concepts of political conflict and non-state conflict actors as well as argues in favor of more rigorous theoretical reasoning. The second part puts the developed concepts to use. It addresses what non-state conflict actors are, how and under what circumstances they emerge, and how they act. The analysis shows that under certain circumstances our intuitive tendency to ascribe agency to collectives is justified. Consequently, the dissertation develops a theory that details the complex relationship between individuals, groups, and social structure. The empirical analysis draws on highly detailed data on inequality, demographic, economic, and geographic characteristics of subnational units, profiles of violence, and armed groups, to explain how inequality leads to the formation of conflict actors and how opportunity structures determine profiles of violence in intrastate conflict. The analysis introduces two new datasets on political conflicts and non-state conflict actors and a new measure of horizontal inequality based on disaggregated, individual-level data.
Keywords: Hochschulschrift